Tendon-Derived Stem Cell Differentiation in the Degenerative Tendon Microenvironment - Chang Liu; Jing-wan Luo; Ke-ke Zhang; Long-xiang Lin; Ting Liang; Zong-ping Luo; Yong-qing Zhuang; Yu-long Sun (Stem Cells International)
Tendinopathy is prevalent in athletic and many occupational populations; nevertheless, the pathogenesis of tendinopathy remains unclear. Tendon-derived stem cells (TDSCs) were regarded as the key culprit for the development of tendinopathy. However, it is uncertain how TDSCs differentiate into adipocytes, chondrocytes, or osteocytes in the degenerative microenvironment of tendinopathy. So in this study, the regulating effects of the degenerative tendon microenvironment on differentiation of TDSCs were investigated. TDSCs were isolated from rat Achilles tendons and were grown on normal and degenerative (prepared by stress-deprived culture) decellularized tendon slices (DTSs). Immunofluorescence staining, H&E staining, real-time PCR, and Western blot were used to delineate the morphology, proliferation, and differentiation of TDSCs in the degenerative microenvironment. It was found that TDSCs were much more spread on the degenerative DTSs than those on normal DTSs. The tenocyte-related markers, COL1 and TNMD, were highly expressed on normal DTSs than the degenerative DTSs. The expression of chondrogenic and osteogenic markers, COL2, SOX9, Runx2, and ALP, was higher on the degenerative DTSs compared with TDSCs on normal DTSs. Furthermore, phosphorylated FAK and ERK1/2 were reduced on degenerative DTSs. In conclusion, this study found that the degenerative tendon microenvironment induced TDSCs to differentiate into chondrogenic and osteogenic lineages. It could be attributed to the cell morphology changes and reduced FAK and ERK1/2 activation in the degenerative microenvironment of tendinopathy.